Medicine, patients and the law. - Brazier, Margaret; Cave, Emma, 1974- (Contemporary issues in bioethics, law and medical humanities., 2025)
'Medicine, Patients and the Law' examines the regulation of medical practice, the rights and duties of patients and their medical advisers, the provision of compensation for medical mishaps and the framework of rules governing medicine and morals.